1998
DOI: 10.1159/000027265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbogen, Oxygen and Intraocular Pressure on Heidelberg Retina Flowmeter Parameter ‘Flow’ Measured at the Papilla

Abstract: The aim of the study was to evaluate whether the Heidelberg retina flowmeter (HRF), a new device for retinal and anterior optic nerve blood flow assessment, can gauge, at least semiquantitatively, a known effect such as an increase in optic nerve blood flow by hypercapnia or a decrease in optic nerve blood flow by hyperoxia or high intraocular pressure (IOP). Measurements with the HRF were obtained at the papilla of three groups of 5 young healthy subjects (1) at baseline and after breathing 5% carbogen, (2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…By using non-invasive technologies such as Scanning Laser Doppler Flowmetry (SLDF) and analysis softwares that produce highly reproducible intrasession and intersession results such as the Automatic Full Field Perfusion Image Analyzer software (AFFPIA-SLDF 3.3, G Michelson, Erlangen, Germany), [12][13][14][15][16][17][18] it is possible to accurately assess the haemodynamic effects of antiglaucomatous drugs.…”
Section: Introductionmentioning
confidence: 99%
“…By using non-invasive technologies such as Scanning Laser Doppler Flowmetry (SLDF) and analysis softwares that produce highly reproducible intrasession and intersession results such as the Automatic Full Field Perfusion Image Analyzer software (AFFPIA-SLDF 3.3, G Michelson, Erlangen, Germany), [12][13][14][15][16][17][18] it is possible to accurately assess the haemodynamic effects of antiglaucomatous drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, confocal scanning laser Doppler flowmetry has been applied to evaluate optic nerve blood flow in glaucoma patients [17, 18]. In addition, it has been shown that the HRF can detect a known effect such as an increase in optic nerve blood flow by hypercapnia or a decrease in optic nerve blood flow by hyperoxia or high intraocular pressure [20]. The present study suggests that blood flow velocities in retrobulbar vessels might be of relevance for optic nerve blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…HRF parameters were computed within a square of 50 × 50 pixels (window of measurement). This was chosen because previous results had demonstrated that, with such a window of measurement, HRF can detect a known effect such as an increase in optic nerve blood flow by hypercapnia or a decrease in optic nerve blood flow by hyperoxia or high intraocular pressure [20]. …”
Section: Methodsmentioning
confidence: 99%
“…In order to test the hypothesis that vasospasm underlies some cases of glaucoma, the known vasodilative effects of hypercapnia 9-12 and vasoconstrictive effects of hyperoxia [12][13][14][15] were used to stimulate autoregulatory responses in the retrobulbar vasculature of normal subjects and glaucoma patients. It was proposed that if the glaucoma patients' vasculature was in a pre-existing reversible vasoconstricted state the glaucoma and normal groups would differ in their response to vasoactive stimuli.…”
mentioning
confidence: 99%